MARITAL ADJUSTMENT, GENDER ROLE PARTNERSHIPS, AND MARITAL SATISFACTION DURING COVID-19 - Dhaifina Annas Tazkiya; Herien Puspitawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
During the Covid-19 pandemic, orders to work and study from home became a problem for families in Indonesia. Marital adjustment and gender role partnerships in the household must be well established to create marital satisfaction so that there is no conflict in the family. This study analyzes the factors influencing marital satisfaction in intact families during the Covid-19 pandemic. Respondents in this study are wives from intact families who have children and are domiciled in the city of Bogor. The sampling technique used non-probability purposive sampling with several samples of as many as 128 people. The data was processed using descriptive and inferential tests and multiple linear regression using SPSS 25 and Structural Equation Modeling (SEM) using SmartPLS 3.0. The correlation test results showed a positive correlation between marital adjustment, gender role partnerships, and marital satisfaction. The results of the linear regression test showed that the husband's income had a significant positive effect on marital satisfaction. Correlation tests, linear regression test results, and SEM showed that marital adjustment and gender role partnerships significantly positively affected marital satisfaction. There is an indirect effect between marital adjustment and marital satisfaction with gender role partnership mediators.